Flat as an investment instrument - Marada, Josef; Radová, Jarmila; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2011)
The bachelor's thesis "Flat as an investment instrument" is focused on buying a flat as an investment. The first part gives practical information, which can help the investor to do the right investment decision. There are described and analyzed individual factors influencing the investment - yield, risk, liquidity and factors with the biggest impact on the flat value. The second part offers an analytical example, which compares the investment into flats in different cities in Czech Republic under the current market conditions. The results are compared according to theirs profitability and commented with a possible explanation. Finally, an example of investment into a concrete flat is included, in order to show the theoretical approaches mentioned in the first part of the thesis. The main objective of the thesis is to introduce a compact overview about investing into flats.
Vedoucí práce: Jarmila Radová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses